Current phenotypic and genetic spectrum of syndromic deafness in Tunisia: paving the way for precision auditory health - Mkaouar, Rahma; Riahi, Zied; Marrakchi, Jihene; Mezzi, Nessrine; Romdhane, Lilia; Boujemaa, Maroua; Dallali, Hamza; Sayeb, Marwa; Lahbib, Saida; Jaouadi, Hager; Boudabbous, Hela; Zekri, Lotfi; et al. (Frontiers in Genetics, 2024)
Hearing impairment (HI) is a prevalent neurosensory condition globally, impacting 5% of the population, with over 50% of congenital cases attributed to genetic etiologies. In Tunisia, HI underdiagnosis prevails, primarily due to limited access to comprehensive clinical tools, particularly for syndromic deafness (SD), characterized by clinical and genetic heterogeneity. This study aimed to uncover the SD spectrum through a 14-year investigation of a Tunisian cohort encompassing over 700 patients from four referral centers (2007 -2021). Employing Sanger sequencing, Targeted Panel Gene Sequencing, and Whole Exome Sequencing, genetic analysis in 30 SD patients identified diagnoses such as Usher syndrome, Waardenburg syndrome, cranio-facial-hand-deafness syndrome, and H syndrome. This latter is a rare genodermatosis characterized by HI, hyperpigmentation, hypertrichosis, and systemic manifestations. A meta-analysis integrating our findings with existing data revealed that nearly 50% of Tunisian SD cases corresponded to rare inherited metabolic disorders. Distinguishing between non-syndromic and syndromic HI poses a challenge, where the age of onset and progression of features significantly impact accurate diagnoses. Despite advancements in local genetic characterization capabilities, certain ultra-rare forms of SD remain underdiagnosed. This research contributes critical insights to inform molecular diagnosis approaches for SD in Tunisia and the broader North-African region, thereby facilitating informed decision-making in clinical practice.